Pengaruh Kepuasan Dan Kepercayaan Terhadap Minat Beli Ulang Pada E-Commerce Shopee (Studi Pada Mahasiswa FEB Unisma Angkatan Tahun 2017) - Fina A’immatur Rifki; Muhammad Ridwan Basalamah; Nurhidayah Nurhidayah (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This research was conducted to determine the effect of Satisfactiom, Trust, on Repurchase at Shopee in the Faculty of Business Economics, Islamic University of Malang. This research uses explanatory research and quantitative approaches. Malhotra's theory is used to take samples, total sample of 90 people is found.To solve the problem in this study, using the validity test, reliability test, normality test, multiple linear regression test, multicollinearity test, heteroscedasticity test, classic assumption test. research using multiple linear regression analysis with the help of SPSS 26. The results of this study are the of Satisfactiom, Trust, affect Repurchase simultaneously, partially the Kepuasan variable has no effect on Impulse Buying, while Shpping Kepercayaan and . partially affect the Impulse Buying at Shopee at the Faculty of Business Economics, Islamic University of Malang. Keywords: Satisfaction and Trust in Buying Interest